Relevansi Teori Kiri Islam Hasan Hanafi dalam Menyingkap Bentuk-Bentuk Hegemoni Barat dalam Dunia Islam - Fahrozi, Albef; Ningsih, Tri Wulan; Ivaro, Jihad Haykal (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze Hasan Hanafi's critique of Western hegemony in the Islamic world by placing Islamic leftist ideas as the main theoretical framework. The research focuses on how Western hegemony operates in the political-economic, educational, and cultural spheres and its implications for the formation of epistemic subordination and structural dependence of Islamic countries. The research method used is a qualitative approach based on library research. The results of the study show that Western hegemony works not only through global economic and political domination, but also through control of knowledge standards, academic language, and cultural production that marginalizes Islamic intellectual traditions. These findings confirm that epistemic subordination is at the core of the structural dependence of the Islamic world. In response, Hasan Hanafi's three-pillar framework of Islam, namely the revitalization of classical Islamic heritage, criticism of Western hegemony, and critical reading of social reality, is offered as a theoretical alternative and strategy for building intellectual autonomy and structural emancipation for Muslims in the contemporary global context.